Dental hospitalisation patterns in stroke and traumatic brain injury patients - Somayyeh Azimi; Dr Lakkhina Troeung; Dr Angelita Martini (Elsevier, 2023)
Aim or Purpose: Traumatic Brain Injury (TBI) and Stroke are two common types of acquired brain injury that lead to significant secondary health issues, including oral health problems (1). This retrospective cohort study aimed to explore dental hospitalisation diagnosis in TBI and stroke patients cohort in Western Australia (WA). Materials and Methods: The cohort comprised 282 TBI and 200 stroke patients enrolled in a rehabilitation service in WA from 1991-2016. De-identified patient data were linked to the Hospital Morbidity Data Collection (HMDC) through the WA Data Linkage System. Dental hospitalisations were ascertained from the primary and secondary diagnoses in the HMDC data using the ICD codes. For all cohort members, a minimum 10-year pre-injury look-back period was available. The mean follow-up post-acute injury was 10.98±9.35 years. Descriptive statistics were used to describe hospitalisation characteristics by injury phase. Chi-square tests were used to compare the prevalence of dental diagnoses between groups. Results: In both TBI and stroke, the incidence of dental hospitalisation increased significantly from pre-injury to both acute and post-acute injury (p<0.001). Stroke patients had a higher incidence rate difference from the pre-injury to the acute phase (0.62 to 145.27/1000PY), and TBI patients had a higher incidence rate difference from the pre-injury to post-acute phase (1.23 to 12.52/1000 PY). In the post-acute phase, caries was the most prevalent diagnosis in both TBI (4.66/1000PY) and stroke (2.93/1000PY), with a significantly higher incidence in TBI (p=0.001). Conclusions: The results highlight differences in dental hospitalisation after stroke and TBI and the need for appropriate and timely oral health care to prevent dental hospitalisations.